Association of CYP7A1 and CYP2E1 Polymorphisms with Type 2 Diabetes in the Chinese Han Populations - Zhang L; Tang J; Wang Y; Wang X; Wang F (Dove Medical Press, 2022)
Lihong Zhang, Jingjing Tang, Yindi Wang, Xiang Wang, Fang Wang Department of Endocrinology, Xi'an Central Hospital Affiliated to Xi'an Jiaotong University, Xi'an, 710003, People's Republic of ChinaCorrespondence: Fang Wang, Department of Endocrinology, Xi'an central hospital affiliated to Xi'an Jiaotong University, No. 185, Houzaimen, Xincheng District, Xi'an, Shaanxi Province, People's Republic of China, Tel/Fax +86 18681809668, Email 2807305710@qq.comBackground: Type 2 diabetes mellitus (T2DM) is caused by diverse environmental and genetic risk factors. Previous studies have reported that cytochrome P450 (CYP) is a promising gene for T2DM. Therefore, we aimed to determine the effects of CYP7A1 and CYP2E1 polymorphisms on T2DM susceptibility among the Chinese Han population.Methods: A case-control study was conducted to assess the potential relationship of four polymorphisms (rs8192879, rs12542233, rs2070672 and rs2515641) with T2DM susceptibility in the Chinese population, involving 512 T2DM patients and 515 age- and gender-matched healthy individuals. We used the Agena MassARRAY platform to detect CYP7A1 and CYP2E1 polymorphisms. The relationship between genetic polymorphisms and T2DM risk was evaluated using odds ratios (ORs) and 95% confidence intervals (CIs) in various genetic models.Results: After adjusting for age and gender, rs12542233 in the CYP7A1 gene was significantly associated with decreased T2DM risk (recessive: OR = 0.67, 95% CI = 0.49- 0.91, p = 0.012; after FDR correction, p = 0.048). The CYP7A1 rs12542233 was associated with a reduced risk of T2DM in people over 59 years of age (p = 0.010). In the population with BMI ≤ 24 kg/m2, CYP7A1 rs12542233 was associated with an increased risk of T2DM (p < 0.05). In the population with BMI > 24 kg/m2, CYP2E1 rs2515641 can significantly reduce the risk of T2DM (p < 0.05). And rs8192879, rs2070672 and rs2515641 could significantly increase the risk of diabetes retinopathy in T2DM patients (p < 0.05). Furthermore, the Trs8192879Crs12542233 haplotype was significantly associated with T2DM (p = 0.019).Conclusion: CYP7A1 and CYP2E1 polymorphisms may contribute to T2DM susceptibility in the Chinese Han population, especially in stratified analysis.Keywords: diabetes mellitus, type 2, gene polymorphisms, case-control study, CYP7A1, CYP2E1